Clinical Impact of Expedited Pathogen Identification and Susceptibility Testing for Gram-negative Bacteremia and Candidemia Using the Accelerate Pheno™ System. (4th October 2017) - Burnham, Jason; Wallace, Meghan; Fuller, Brian; Burnham, Carey-Ann D; Kollef, Marin
Abstract: Background: Inappropriate initial antibiotic therapy (IIAT) for sepsis increases mortality. Fast diagnostic tests providing earlier identification (ID) of pathogens and antimicrobial susceptibility testing (AST) have the potential to improve mortality and antimicrobial stewardship. The Accelerate Pheno™ system (AXDX) is a newly FDA cleared fast diagnostic testing system that provides ID and AST for Gram-positive and Gram-negative bacteria (GNB) and ID for Candida bloodstream isolates. Methods: From April 14, 2016 to March 13, 2017, blood cultures from unique patients in the emergency department or medical intensive care units at Barnes-Jewish Hospital signaling positive and Gram-stain positive for GNB or yeast were eligible for inclusion. Standard-of-care (SOC) diagnostics were conducted in parallel with AXDX, though AXDX could be delayed up to 8 hours depending on research technician availability. Differences in time to ID and AST between SOC and AXDX were determined. Clinical outcomes included appropriateness of initial empiric antimicrobial therapy, potential for early antimicrobial de-escalation with AXDX, and mortality. Results: Of 341 screened blood cultures, 123 met inclusion criteria; 101 had organisms that were on-panel for AXDX, 88 GNB and 13 C. glabrata or C. albicans . For GNB, mean time from blood culture positivity to ID and AST using SOC was 19.8 and 53.5 hours, respectively, and 1.4 and 6.7 hours using AXDX (from time AXDX started). For Candida spp., mean time to ID was 33.1 hours for SOC, 1.4 hours for AXDX. Antimicrobial de-escalation was possible based on AXDX testing in 52.9% of patients with GNB infections. A total of 27 (27.3%) patients received IIAT. In-hospital mortality was higher (48.1%) in the IIAT group than in those receiving appropriate initial antibiotics (12.5%), P < 0.001. AXDX could have improved antimicrobial therapy in 89.8% of GNB and 92.3% of Candida spp. cases. Conclusion: The Accelerate Pheno™ system is a novel fast diagnostic that significantly reduces the time to ID and AST for GNB and ID of Candida spp. bloodstream infections, with the potential to impact clinical outcomes. Prospective clinical trials are needed to evaluate the impact of this new system on clinical outcomes and antimicrobial stewardship. Disclosures: C. A. D. Burnham, Accelerate Diagnostics: Investigator, Research support; M. Kollef, Accelerate Diagnostics: Consultant, Research support